The impact of customer value co-creation and relationship quality on relationship equity : personality traits as a moderator - Nor Asiah Omar,; Ahmad Sabri Kassim,; Muhamad Azrin Nazri,; Farhana Sidek, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study aimed to examine the relationship among customer value co-creation, relationship quality, and relationship equity in the tailoring services in Malaysia. Moreover, this study also investigated whether customer personality trait plays a moderating role in the relationship of value co-creation behavior and relationship quality as well as the relationship between relationship quality and relationship equity. A total of 245 questionnaires were collected via purposive sampling from customers seeking tailoring services from SME tailoring businesses. The findings revealed that customer value co-creation has a statistically significant influence on relationship quality. In addition, relationship quality was also positively related to relationship equity. However, the moderating effect of customer personality trait was not significant. This study contributes to the existing literature on customer co-creation and personality traits of consumers in tailoring services of SMEs, particularly in explaining the relationship equity of consumers.